مستوى امتلاك معلمات الإعاقة الفكرية لكفايات استخدام التعليم عن بعد في تعليم ذوي الإعاقة الفكرية في ظل جائحة كورونا - السواط، رحاب معيض; عطا، حسنين علي يونس (مؤسسة التربية الخاصة والتأهيل, 2023)
هدفت الدراسة إلى التعرف على مستوى امتلاك معلمات الإعاقة الفكرية لكفايات التعليم عن بعد في تعليم ذوي الإعاقة الفكرية في ظل جائحة كورونا. واستخدمت الدراسة المنهج الوصفي المسحي. كما استخدمت الاستبانة كأداة لجمع البيانات (من إعداد الباحثة)، تم تطبيقها على عينة بلغ عدد أفرادها (۹۱) معلمة لذوي الإعاقة الفكرية بمدينة الطائف. وأظهرت النتائج أن معلمات التربية الفكرية يمتلكن جميع كفايات استخدام التعليم عن بعد بدرجة عالية جدا، بمتوسط بلغ (٤,٣٥ من ٥,٠٠). وقد جاء مستوى امتلاك المعلمات لكفايات تقديم الدروس عن بعد في الترتيب الأول بمتوسط (٤,٤١)، في حين جاء مستوى امتلاك المعلمات لكفايات إعداد الدروس عن بعد في المرتبة الثانية بمتوسط (٤,٣٩)، كما جاء مستوى امتلاك المعلمات لكفايات استخدام منصات التعليم عن بعد في المرتبة الثالثة بمتوسط (٤,٣٣)، وجاء مستوى امتلاك المعلمات لكفايات تقييم الطلاب ذوي الإعاقة الفكرية عن بعد في المرتبة الرابعة والأخيرة بمتوسط (٤,٢٨). كما توصلت الدراسة إلى عدم وجود فروق في استجابة معلمات الإعاقة الفكرية على مقياس كفايات استخدام التعليم عن بعد وأبعاده تعود لمتغير المكان التعليمي (مدرسة دمج - معهد التربية الفكرية)، ومتغير المؤهل الدراسي (بكالوريوس - دبلوم عال - دراسات عليا). وكذلك عدم وجود فروق في استجابة المعلمات في بعدي (كفايات استخدام منصات التعليم عن بعد، كفايات إعداد الدروس عن بعد) تعود لمتغير مستوى الخبرة (من ١- ١٠ سنوات، أكثر من ١٠ سنوات)، في حين وجدت فروق ذات دلالة إحصائية عند مستوى دلالة (٠,٠٥) ، في بعدي (كفايات تقديم الدروس عن بعد، وكفايات تقييم الطلاب عبر منصات التعليم عن بعد) باختلاف متغير مستوى الخبرة لصالح أفراد عينة الدراسة من المعلمات ذوات الخبرة من (1- 10) سنوات. وأوصت الدراسة بضرورة ربط تقويم الأداء الوظيفي للمعلمات بحضور دورات تدريبية متخصصة في مجال التعليم عن بعد، وتطوير البرامج الخاصة باستخدام التعلم الإلكتروني في التعلم عن بعد، والتوسع فيه. The study aimed to identify the level of female teachers for those with intellectual disability possession of distance education competencies in teaching people with intellectual disabilities in light of the COVID-19. The study adopted the descriptive survey method. The researcher used the questionnaire as a tool for data collection (prepared by the researcher) and it was applied to a sample of (91) female teachers for those with intellectual disabilities in Taif. The results concluded that teachers for those with intellectual disabilities possessed all the competencies of using distance education with a "very high" degree and with an arithmetic mean (4.35 out of 5.00). The level of teachers' possession of the competencies of giving distance lessons came in the first rank with an arithmetic mean of (4.41), while the level of teachers’ possession of competencies of preparing distance lessons came in the second rank with an arithmetic mean of (4.39), and the level of teachers’ possession of the competencies of using distance education platforms came in the third rank with an arithmetic mean of (4.33), and the level of teachers’ possession of the competencies of evaluating students with intellectual disability from a distance came in the fourth and final rank with an arithmetic mean of (4.28). The study also concluded that there were no differences in the response of the teachers for those with intellectual disability on the scale of competencies of using distance education and its dimensions due to the variable of the educational location (inclusion school- Institute of Intellectual Education) and the academic qualification variable (Bachelor- Higher Diploma- Postgraduate). Also, there were no differences in the response of teachers in the two dimensions (competencies of using distance education platforms, competencies of preparing distance lessons) due to the variable of the level of experience (from 1-10 years, more than 10 years). There were statistically significant differences at the significance level (0.05), in the two dimensions (competencies of giving distance lessons, and competencies of evaluating students with intellectual disability from a distance) due to the level of experience variable for the study sample members of teachers with experience (1- 10) years. The study recommended the necessity of linking teachers’ job performance evaluation by attending training courses in the field of distance education and developing programs for using e-learning in distance education.
Keywords: ذوي الاحتياجات الخاصة -- التعليم الإلكتروني -- الإعاقة الفكرية -- التربية الخاصة